Failed Rescue Mission, Child Prostitution and Resuccumbing Factors in Gauteng, South Africa - Kevin Sibanyoni, Ephraim; Angel Olofinbiyi, Sogo (International Journal of Criminology and Sociology, 2022)
The study describes child prostitution as the worst violation of fundamental Human Rights – a pervasive trend that has been synonymous to modern form of slavery. There is evidence that children usually get initiated into prostitution either by being abducted or lured by promises of certain existential needs of life. Despite the degree at which prostitution renders children and youths vulnerable to physical health crises and psychological harm, they still resuccumb to prostitution after having been rescued by organizations of concern. It was discovered that most of the children that participated in the questionnaire-based survey had been rescued from prostitution more than once in their respective lifetimes. The study established that children’s resuccumbing to prostitution is precipitated by factors such as money, drugs and alcohol addiction, as well as a sense of independence. The study recommends further research inquiries to be undertaken to better understand the intricacies associated with sexual exploitation of children and provide more effective and culturally sensitive measures to prevent affected children from these unscrupulous practices. Strengthening the effectiveness of counselling techniques in rehabilitating sexually exploited children is another way forward.